A Revised Definition of Games: An Analysis of Grasshopper Errors, Omissions, and Ambiguities. Issue 3 (2nd October 2019) - Kretchmar, Scott
ABSTRACT: In this essay, I review Suits' classic description of games and cite three kinds of problems—mischaracterizations, omissions, and ambiguities. I build on previous criticisms by myself and others leveled at his definition. However, in contrast to much of this previous work, I will present what I hope is an improved description. The latter part of the essay is devoted to defending this alternate characterization. I conclude by arguing that my revisionist work paradoxically both supports and undermines the merits of Suits' anti-Wittgensteinian efforts to identify the necessary and sufficient conditions for games.